Pengaruh Modal Intelektual, Kepemilikan Institusional, Pertumbuhan Perusahaan, Ukuran Perusahaan dan Leverage Terhadap Kinerja Perusahaan - Nur Hidayah; Hermanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the influence of intellectual capital (IC), institutional ownership (IO), company growth (SG), company size (TA), and leverage (DER) on company performance in the food and beverage sub-sector industry listed on the Indonesia Stock Exchange (IDX) in 2019-2023. Data were obtained from the company's annual financial reports published, with a total of 85 data from 17 companies selected as samples using purposive sampling techniques. Data analysis through multiple linear regression using the SPSS statistical data processing application. The results of the study illustrate that intellectual capital, company growth, and company size have no influence on company performance. Then, institutional ownership has a significant positive impact on company performance. Meanwhile, leverage has a significant negative impact on company performance.